Direct immunofluorescence as low-budget method for brain tissue inspection in standardization of neuroborreliosis animal model in NMRI mice - Djuric, Selena; Simin, Verica; Banović, Pavle (PONS - medicinski časopis, 2021)
Goal. To test if the direct immunofluorescence can be used for the detection of Borrelia afzelii in brain tissue during the standardization of the animal model of neuroborreliosis in NMRI mice. Methods. The experiment included 15 NMRI mice. Borrelia afzelii was cultivated in BSK-H medium, and 100 µl of the medium was injected subcutaneously in every mouse. To determine the Borrelia infection in mice, brains were collected in III(n=4), IV(n=6) and V(n=5) weeks after the inoculation. All animals were sacrificed using cervical dislocation. Brain tissue was analysed with direct immunofluorescence and polymerase chain reaction (PCR). Results. The first brain tested positive for Borrelia three weeks after the inoculation. The bacteria were detected in 1 out of 4 brains (25%). After that, there was a growth in the percentage of positive results. The data showed that 3 out of 6 brains (50%) were found positive on Borrelia presence by the end of the fourth week. Whereas, in 3 out of 5 brains (60%) Borrelia was detected five weeks following the inoculation. Conclusion. According to the preliminary results, direct immunofluorescence appeared to be a practical, low budget method for following the kinetics of neuro-infection. NMRI mice could be considered as an adequate animal model for neuroborreliosis. Thus, more research is needed on the topics of infection kinetics for the period after fifth week post inoculation, as well as sensitivity and specificity of direct immunofluorescence.